2021
DOI: 10.1080/02513625.2021.1981012
|View full text |Cite
|
Sign up to set email alerts
|

Features and Consequences of Flat Ontology in Expanded Urban Planning

Abstract: Sirkku Wallin, PhD in Science (Spatial Planning and Transportation Engineering), is a visiting scholar at the Department of Built Environment, Aalto University, Finland. She is also a planning practitioner at the City of Espoo. The focus of her research is self-organised urban development and e-planning.Karolina Jarenko, M.Sc. in Political Philosophy, is a PhD student at the Department of Built Environment, Aalto University, Finland. She studies and helps develop self-organising and self-governing organisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 19 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Therefore, 'pluralist realism without borders' is a suitable starting point for expanded urban planning, as it increases the extent and scope of urban planning. This was corroborated by the Nordic case studies in Wallin et al [6], as they showed a variety of foci-from spatial planning to community development and hybrid governance, including different phases and varieties of self-organising-depending on the purpose and context.…”
Section: Flat Ontology and Expanded Urban Planning As A Theoretical F...mentioning
confidence: 64%
See 4 more Smart Citations
“…Therefore, 'pluralist realism without borders' is a suitable starting point for expanded urban planning, as it increases the extent and scope of urban planning. This was corroborated by the Nordic case studies in Wallin et al [6], as they showed a variety of foci-from spatial planning to community development and hybrid governance, including different phases and varieties of self-organising-depending on the purpose and context.…”
Section: Flat Ontology and Expanded Urban Planning As A Theoretical F...mentioning
confidence: 64%
“…Thus, ontological engagement affects premises, which have consequences for one's aspirations regarding urban planning and development. In a recent article, we examined [6] the core features of flat ontology for expanded urban planning. We concluded that flat ontology should be called fat, as it makes the conceptualisation of planning manifold and deliberative instead of linear and hierarchical [6].…”
Section: Flat Ontology and Expanded Urban Planning As A Theoretical F...mentioning
confidence: 99%
See 3 more Smart Citations